2012
DOI: 10.5230/jgc.2012.12.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for Postoperative Morbidity in Perforated Peptic Ulcer

Abstract: Purpose Emergency operations for perforated peptic ulcer are associated with a high incidence of postoperative complications. While several studies have investigated the impact of perioperative risk factors and underlying diseases on the postoperative morbidity after abdominal surgery, only a few have analyzed their role in perforated peptic ulcer disease. The purpose of this study was to determine any possible associations between postoperative morbidity and comorbid disease or perioperative risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 17 publications
(20 reference statements)
8
35
2
1
Order By: Relevance
“…There are studies indicating that morbidity rates increase depending on the presence of concomitant diseases in patients with peptic ulcer perforation (12,(27)(28)(29). Similarly, we identified that our patients who had concomitant diseases had higher morbidity rates.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…There are studies indicating that morbidity rates increase depending on the presence of concomitant diseases in patients with peptic ulcer perforation (12,(27)(28)(29). Similarly, we identified that our patients who had concomitant diseases had higher morbidity rates.…”
Section: Discussionsupporting
confidence: 57%
“…Parallel with the literature, our patients were identified to have wound site infections and pulmonary complications. We found in our study that age above 60, presence of a concomi- Kim et al (27) stated that age above 60 and female sex constituted the risk factors that influenced post-operative morbidity. In our study, PUP was often seen among men whereas sex was not a significantly influencing factor for morbidity.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…[1][2][3] A large number of prognostic factors for morbidity and mortality in patients with perforated peptic ulcer have been reported. [2][3][4][5][6][7] Several clinical scoring system have been proposed for prognostic prediction. The most wellknown predicted scoring system is Boey score 3, which predicted mortality in PPU patients base on the time from perforation to admission, pre-operative systolic blood pressure and comorbid conditions of patients.…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between DM and rebleeding in PUB was reported in two articles (3,27). Three articles mentioned that perforated peptic ulcer was associated with DM (3,33,34). Three other related investigations were involved in the present study (6,35,36).…”
Section: Study Selectionmentioning
confidence: 99%